Analisis Kesiapsiagaan Ibu Rumah Tangga dalam Pencegahan Stunting Ditinjau Pemberian ASI Eksklusif dan Sanitasi : Analisis Kesiapsiagaan Ibu Rumah Tangga dalam Pencegahan Stunting Ditinjau Pemberian ASI Eksklusif dan Sanitasi - Wiratama, Rifki; Wulandari, Endah Sri (Afiasi : Jurnal Kesehatan Masyarakat, 2024)
Stunting is a condition that indicates growth failure in children due to chronic malnutrition, recurrent infections, and inadequate psychosocial stimulation. If left untreated, stunting can lead to impaired physical development and hurt cognitive development, educational performance, and even economic productivity in adulthood. This study aims to analyze housewives' preparedness to prevent stunting, viewed from aspects of sanitation and exclusive breastfeeding in Cikunir Village, Tasikmalaya Regency. The research method used is a quantitative approach with a descriptive-analytical design. Data were collected from 39 housewife respondents who have children under five years old through questionnaires and direct observation. Data analysis was performed using the Spearman correlation test. The study results show that exclusive breastfeeding has a significant positive correlation with the occurrence of stunting (p-value=0.042), as does access to clean water (p-value=0.001) and access to restrooms (p-value=0.016), while the type of restroom was not significant (p-value=0.060). These findings indicate that access to clean water has a highly significant relationship with the incidence of stunting in children under five years old. However, the type of restroom was not significantly associated with stunting. In conclusion, the low prevalence of stunting in the study location is likely due to the limited practice of exclusive breastfeeding and sanitation access. Furthermore, efforts should be prioritized to increase the coverage of exclusive breastfeeding, provide adequate sanitation access, and raise community awareness about restroom sanitation and the surrounding environment to further reduce the incidence of stunting.